SUCCESSFUL PREGNACY OUTCOME IN A CASE OF OSTEOGENESIS IMPERFECTA WITH HIPOPITUITARISMUS - Azemi Neziri, Ruhide; Simeonova Krstevska, Slagjana; Todorova, Biljana; Bojadziev, Aleksandar (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Case report Osteogenesis imperfecta (OI), first described in the seventeenth century, is a rare inherited connective tissue disease, characterized by bone fragility, low bone mass, and susceptibility to bone fractures with variable severity. Osteogenesis imperfecta (OI) or brittle bone disease is a phenotypically diverse disorder caused by deficiencies in the synthesis of type I collagen. We present hereby a case of a pregnant woman with osteogenesis imperfecta and hypopituitarismus. Pregnancy was achieved with IVF procedure, and hypertension occurred in the 32nd gestational week of pregnancy. A multidisciplinary team approach was mandatory and resulted in the delivery of a live baby girl in the 37th gestational week of pregnancy. The successful outcome of this high-risk pregnancy and delivery can be attributed to collaboration between different specialty teams and planning for the known complications that may affect pregnancy and delivery in women with these genetic skeletal disorders. Keywords: hypopituitarismus, osteogenesis imperfecta, pregnancy, childbirth